IMPLEMENTING LEAN SIX SIGMA IN THE PALESTINE POULTRY COMPANY - Huthaifa Abu Shhade; Mohammad AbdAljaleel; Rema' Bsharat; Shahed Zedan; Leena Alatrash (My University, 2016)
Lean six sigma principles have been successfully applied to manufactured products for several decades. It's one of the quality improvement strategies that focuses on identifying and eliminating any unnecessary waste in particular system and increase manufacturing revenue by stream lining process. In this project we will apply lean six sigma philosophy on one of the most famous factories in Palestine, Palestine Poultry Company (AZIZA) which located in Tulkarm city. For any industrial facility, the main reason of using these principles is to maintain a continuous improvement on facility performance. One of the main points is reducing the gap which is (6 ton) between planned (25 ton) and current (19 ton) and time which causes by the gap, also increasing the production capacity required, that lead to revenue increase . So the target of our project is using lean six sigma principles to eliminate waste time and reduce the gap, in the other word increasing revenues. To achieve this, we will follow this methodology: first of all, we need to study the current situation of AZIZA factory, then to DMAIC phases of the lean six sigma manufacturing process and concept. Finally,  a various of solutions will be implemented, to achieve the main target of this project.

(Lean six sigma) . .   (Lean six sigma)  (AZIZA) . . (6 ) (25 )  (19 ) . (Lean six sigma) . : AZIZA DMAIC .
IMPLEMENTING LEAN SIX SIGMA IN THE PALESTINE POULTRY COMPANY